A negative electrode active material, a preparation method thereof, and a sodium ion battery

By combining a porous core with a soft carbon shell, the design of the negative electrode active material solves the problems of low specific capacity and low initial coulombic efficiency in sodium-ion batteries, achieving high-efficiency battery performance and stability while reducing costs.

CN120527377BActive Publication Date: 2025-11-18INNER MONGOLIA SINUO NEW MATERIAL TECH CO

Patent Information

Application Number
CN202511022565.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-11-18
Estimated Expiration
2045-07-24

AI Technical Summary

Technical Problem

Existing sodium-ion battery anode materials have low specific capacity, initial coulombic efficiency, and rate performance, and the poor compositional consistency of pitch-based hard carbon materials leads to unstable battery performance.

Method used

By combining porous core materials with soft carbon shell materials, and by controlling the porosity and micropore ratio, along with a specific heat treatment process, a negative electrode active material with an appropriate specific surface area is prepared, thereby reducing the electrolyte contact area and minimizing side reactions.

Benefits of technology

It improves the specific capacity, initial coulombic efficiency, and rate performance of sodium-ion batteries, enhances the charge-discharge efficiency and cycle stability of the batteries, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120527377B_ABST
    Figure CN120527377B_ABST
Patent Text Reader

Abstract

The application discloses a kind of negative active material and its preparation method and sodium ion battery, it is related to battery preparation technical field, the negative active material includes porous inner core material and at least fill in the shell material in the porous inner core material pore;The porous inner core material includes porous hard carbon, and the shell material includes soft carbon;The porosity of the negative active material is 46~63%, and the proportion of micropore in the pore of the negative active material is 55~72%.The porosity and micropore proportion of the negative active material of the application can guarantee that the specific capacity of sodium ion battery is higher, the rate is higher and the first coulomb efficiency is high in the above range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery manufacturing technology, and in particular to a negative electrode active material, its preparation method, and a sodium-ion battery. Background Technology

[0002] Sodium-ion batteries, as a novel energy storage technology, are considered the most ideal alternative to lithium-ion batteries in the field of new energy due to their low cost, high safety, and abundant sodium resources in nature.

[0003] In sodium-ion batteries, the choice of anode material directly affects the battery's energy density, cycle life, and stability. Hard carbon, with its high sodium storage capacity and good cycle stability, is a superior anode material for sodium-ion batteries. Pitch is a precursor to hard carbon, offering advantages such as low cost, readily available raw materials, and high carbon yield. However, in actual preparation, it has been found that pitch's composition is complex due to the influence of its raw material (coal or petroleum) origin, leading to inconsistent performance during preparation. Furthermore, direct high-temperature pyrolysis and carbonization of pitch-based hard carbon materials yields carbon with a high degree of graphitization, which reduces the interlayer spacing and thus lowers its sodium storage capacity. These defects ultimately result in lower specific capacity, initial coulombic efficiency, and rate performance of pitch-based hard carbon anode materials, reducing their practicality. Summary of the Invention

[0004] The main objective of this invention is to propose a negative electrode active material, its preparation method, and a sodium-ion battery, aiming to solve the problems of low specific capacity, initial coulombic efficiency, and rate performance of carbon negative electrode materials in the prior art.

[0005] To achieve the above objectives, the present invention proposes a negative electrode active material, the negative electrode active material comprising a porous core material and a shell material at least filling the pores of the porous core material;

[0006] The porous core material includes porous hard carbon, and the shell material includes soft carbon.

[0007] The porosity of the negative electrode active material is 46%~63%, and the proportion of micropores in the pores of the negative electrode active material is 55%~72%.

[0008] In one embodiment, the average pore size of the micropores is 2.1~4.0 Å; and / or,

[0009] The specific surface area of ​​the negative electrode active material is 2~25m². 2 / g; and / or,

[0010] The mass ratio of the porous material to the shell material is 7:1 to 20:1.

[0011] This invention also provides a method for preparing a negative electrode active material, comprising the following steps:

[0012] S1. The first asphalt powder is subjected to a first heat treatment under negative pressure and then cooled to obtain a first intermediate.

[0013] S2. Under inert gas conditions, the first intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

[0014] In one embodiment, step S2 includes:

[0015] S21. Mix the first intermediate, the oxygen-containing compound and water, perform a second heat treatment, and cool to obtain the second intermediate;

[0016] S22. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

[0017] In one embodiment, step S22 includes:

[0018] S221. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain hard carbon;

[0019] S222. The hard carbon is mixed with an organic solution containing the second asphalt powder, the organic solvent is removed, and a mixture is obtained. The mixture is then subjected to a second carbonization treatment to obtain a negative electrode active material.

[0020] In one embodiment, the temperature of the first carbonization treatment is greater than the temperature of the second carbonization treatment; and / or,

[0021] The softening point temperature of the first asphalt powder is higher than that of the second asphalt powder.

[0022] In one embodiment, the softening point temperature of the first asphalt powder is 180~350℃; and / or,

[0023] The softening point temperature of the second asphalt powder is 60~250℃.

[0024] In one embodiment, in step S1, the temperature of the first heat treatment is 300~550°C; and / or,

[0025] In step S1, the duration of the first heat treatment is 2-4 hours; and / or,

[0026] In step S1, the particle size distribution of the first asphalt powder is D90 ≤ 10 mm; and / or,

[0027] In step S21, the oxygen-containing compound includes one or more of the following: sulfuric acid, nitric acid, phosphoric acid, potassium permanganate, acetic acid, ethylene glycol, glycerol, pentaerythritol, ethyl acetate, formaldehyde, paraformaldehyde, p-hydroxybenzaldehyde, sulfur, p-formaldehyde, sodium hydroxide, potassium hydroxide, and lithium hydroxide; and / or,

[0028] In step S21, the temperature of the second heat treatment is 120~150℃; and / or,

[0029] In step S21, the duration of the second heat treatment is 2-8 hours; and / or,

[0030] In step S21, the mass ratio of the first intermediate, the oxygen-containing compound, and the water is 0.5:1:10 to 5:1:10; and / or,

[0031] In step S21, the particle size distribution of the first intermediate is D10≥5μm, D50≤12μm, and D90≤40μm.

[0032] In one embodiment, in step S221, the inert gas includes one or more of argon, nitrogen, carbon dioxide, and hydrogen; and / or,

[0033] In step S221, the temperature of the first carbonization treatment is 1000~1800℃; and / or,

[0034] In step S221, the first carbonization treatment takes 2-4 hours; and / or,

[0035] In step S222, the organic solvent includes one or more of kerosene, gasoline, diesel, tetrahydrofuran, petroleum ether, methyl chloride, xylene, acetone, methanol, ethanol, n-hexane, carbon tetrachloride, carbon disulfide, turpentine, and benzene; and / or,

[0036] In step S222, the mass ratio of the hard carbon, the organic solution containing the second asphalt powder, and the organic solution containing the second asphalt powder is 5:20:0.1 to 5:40:0.5; and / or,

[0037] In step S222, the temperature of the second carbonization treatment is 1000~1800℃; and / or,

[0038] In step S222, the second carbonization treatment takes 2 to 8 hours.

[0039] The present invention also provides a sodium-ion battery, wherein the sodium-ion battery comprises the aforementioned negative electrode active material or the negative electrode active material prepared by the aforementioned method for preparing the negative electrode active material.

[0040] In the technical solution of this invention, the filling or even coating of porous core materials with soft carbon can reduce the specific surface area of ​​the negative electrode active material, thereby effectively reducing the direct contact area between the negative electrode material and the electrolyte, reducing the probability of side reactions such as electrolyte decomposition, reducing the loss of negative electrode active material, improving the initial coulombic efficiency of the battery, and thus reducing costs. The porosity and micropore ratio of the negative electrode active material of this invention, within the above-mentioned range, can ensure high specific capacity, high rate capability, and high initial coulombic efficiency of the sodium-ion battery. Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0042] Figure 1 This is a scanning electron microscope image of the negative electrode active material prepared in Example 1 of the present invention;

[0043] Figure 2 This is a test diagram of the interlayer spacing of the negative electrode active material prepared in Example 1 of the present invention;

[0044] Figure 3 This is the first charge-discharge curve of the negative electrode active material prepared in Example 1 of the present invention.

[0045] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0047] Sodium-ion batteries, as a novel energy storage technology, are considered the most ideal alternative to lithium-ion batteries in the field of new energy due to their low cost, high safety, and abundant sodium resources in nature.

[0048] In sodium-ion batteries, the choice of anode material directly affects the battery's energy density, cycle life, and thermal stability. Hard carbon, with its high sodium storage capacity and good cycle stability, is a superior anode material for sodium-ion batteries. Pitch pitch is a precursor to hard carbon, offering advantages such as low cost, readily available raw materials, and high carbon yield. However, in actual preparation, direct high-temperature pyrolysis and carbonization of pitch-based hard carbon materials yields carbon with a high degree of graphitization, which reduces the interlayer spacing and thus lowers its sodium storage capacity. Furthermore, pitch materials have a complex composition, making them prone to inconsistent performance during preparation.

[0049] Current methods for improving the sodium storage performance of asphalt-based hard carbon include: (1) using bifunctional activators to form abundant, relatively closed nanopores in hard carbon during high-temperature carbonization; and (2) using sodium chloride-assisted pre-oxidation to promote the oxidative cross-linking reaction of asphalt, inhibit the rearrangement of asphalt molecular structure, reduce the graphitization degree of hard carbon, increase interlayer spacing, and introduce abundant C=O groups and closed-pore structures. However, the specific capacity, initial coulombic efficiency, and rate performance of the hard carbon anode materials obtained by these methods are still insufficient.

[0050] In view of this, the present invention proposes a negative electrode active material, the negative electrode active material comprising a porous core material and a shell material at least filling the pores of the porous core material; the porous core material comprises porous hard carbon, and the shell material comprises soft carbon; the porosity of the negative electrode active material is 46%~63%, and the proportion of micropores in the pores of the negative electrode active material is 55%~72%.

[0051] In the technical solution of this invention, the filling or even coating of porous core materials with soft carbon can reduce the specific surface area of ​​the negative electrode active material, thereby effectively reducing the direct contact area between the negative electrode material and the electrolyte, reducing the probability of side reactions such as electrolyte decomposition, reducing the loss of negative electrode active material, improving the initial coulombic efficiency of the battery, and thus reducing costs. The porosity and micropore ratio of the negative electrode active material of this invention, within the above-mentioned range, can ensure high specific capacity, high rate capability, and high initial coulombic efficiency of the sodium-ion battery.

[0052] In some embodiments, the average pore size of the micropores is 2.1–4.0 Å. The specific surface area of ​​the negative electrode active material is 2–25 m². 2 / g. It is understandable that when the average pore size of the micropores and the specific surface area of ​​the negative electrode active material are within the above range, it facilitates the insertion and extraction of sodium ions, effectively improving the charge and discharge efficiency and cycle stability of the battery.

[0053] In some embodiments, the mass ratio of the porous material to the shell material is 7:1 to 20:1. A mass ratio within this range ensures a suitable ratio of soft carbon to hard carbon, resulting in a lower specific surface area of ​​the negative electrode active material and a higher initial coulombic efficiency.

[0054] This invention also provides a method for preparing a negative electrode active material, comprising the following steps:

[0055] Step S1: The first asphalt powder is subjected to a first heat treatment under negative pressure and then cooled to obtain the first intermediate.

[0056] Step S2: Under inert gas conditions, the first intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

[0057] In the technical solution of this invention, in step S1, the first asphalt powder is subjected to a first heat treatment under negative pressure to rapidly remove light components such as short-chain alkanes and volatile organic compounds from the first asphalt powder. Negative pressure can increase the removal rate of light components. After the low molecular weight light components volatilize and decompose, the residue in the first asphalt powder will undergo preliminary condensation and carbonization to form a first intermediate with a relatively complex structure, thus improving the consistency of the first intermediate. In step S2, the first intermediate is subjected to a first carbonization treatment in an inert atmosphere to avoid the first intermediate being oxidized to generate byproducts, resulting in a negative electrode active material with good consistency. In addition, in the preparation method of this invention, the removal of light components avoids their decomposition during the first charge and discharge, which would form a thick and unstable SEI film and consume a large amount of sodium ions. On the one hand, this improves the initial coulombic efficiency, and on the other hand, the negative electrode active material maintains a high specific capacity. High material consistency also means that there are small structural differences between particles, more consistent ion / electron transport paths, reduced local impedance, and a higher rate capability of the negative electrode active material.

[0058] In some embodiments, step S2 includes:

[0059] Step S21: Mix the first intermediate, the oxygen-containing compound, and water, perform a second heat treatment, and cool to obtain the second intermediate;

[0060] Step S22: Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

[0061] In the technical solution of the present invention, in step S21, the first intermediate, the oxygen-containing compound, and water are mixed and subjected to a second heat treatment. The oxygen-containing compound provides inert oxygen elements, which promotes the oxidative crosslinking of the remaining heavy asphalt components in the first intermediate to obtain the second intermediate. The addition of the oxygen-containing compound improves the consistency of the second intermediate. In step S22, the second intermediate is subjected to a first carbonization treatment in an inert atmosphere. The oxygen-containing functional groups of the oxygen-containing compound prevent the carbon layers of the second intermediate from arranging in an orderly manner during the first carbonization process, thereby producing a hard carbon structure with a low degree of graphitization. This hard carbon structure has a large number of micropores.

[0062] In some embodiments, step S22 includes:

[0063] Step S221: Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain hard carbon;

[0064] Step S222: Mix the hard carbon with an organic solution containing the second asphalt powder, remove the organic solvent to obtain a mixture, and subject the mixture to a second carbonization treatment to obtain a negative electrode active material.

[0065] In the technical solution of the present invention, in step S222, hard carbon is mixed with an organic solution containing second asphalt powder, so that the second asphalt powder enters the mesopores and macropores of hard carbon along with the organic solvent. After the organic solvent is removed, the second asphalt powder remains in the mesopores and macropores of hard carbon and is subjected to a second carbonization treatment. The second asphalt powder will be transformed into soft carbon with a high degree of graphitization at the carbonization temperature. The final composite material in which soft carbon fills part of the pores of hard carbon is the negative electrode active material.

[0066] Understandably, in existing technologies, crosslinking via oxygen typically involves introducing air, which presents numerous uncontrollable factors, including airflow rate, air velocity, and the contact area between air and asphalt. These factors can affect the consistency of the negative electrode active material; in other words, excessively reactive oxygen can lead to a decrease in yield. However, by using the oxygen-containing compound described in this application, the oxygen content can be better controlled, allowing the heavy components in the asphalt to crosslink at a more uniform rate, resulting in higher consistency of the hard carbon material and a higher product yield.

[0067] Understandably, asphalt is a complex mixture, often classified or graded by its softening point. This classification results in inconsistent compositions even within the same grade of asphalt, and even different batches of the same grade from the same manufacturer may differ. The method of this invention removes these complex and uneven small-molecule components, preventing them from hindering the formation of hard carbon structures and causing numerous irregular macropores or mesopores, thus minimizing their impact on the final product and improving its consistency.

[0068] Understandably, soft carbon refers to carbon with low crystallinity, where the layered structure is easier to arrange neatly and, under certain conditions, can form an ordered layered structure close to that of graphite; hard carbon refers to carbon that cannot be graphitized, which cannot form a completely ordered graphite structure even at very high temperatures and has a highly disordered internal structure.

[0069] The raw materials used in the preparation method of this invention are all industrial-grade, abundant, and inexpensive; the equipment used is simple and consists of equipment suitable for continuous industrial production, making it easy to industrialize. The negative electrode active material prepared by the method of this invention effectively improves specific capacity, rate capability, and initial coulombic efficiency.

[0070] In some embodiments, the temperature of the first carbonization treatment is higher than the temperature of the second carbonization treatment. It is understood that the introduction of oxygen-containing functional groups before the first carbonization treatment results in a higher oxygen content in the system. A high oxygen content affects the initial coulombic efficiency and cycle stability of the battery prepared from the negative electrode active material. By setting a higher temperature for the first carbonization treatment, sufficient crosslinking and carbonization can be ensured on the one hand, while reducing the oxygen content in the system on the other. The second carbonization treatment mainly carbonizes the second pitch powder filling the pores of the hard carbon, reducing mesopores and macropores while protecting micropores. This is primarily to reduce the specific surface area of ​​the hard carbon; therefore, the carbonization temperature does not need to be too high.

[0071] In some embodiments, the softening point temperature of the first asphalt powder is higher than that of the second asphalt powder. The first asphalt powder is the main hard carbon raw material, and the second asphalt powder is a soft carbon raw material used for filling or coating. The softening point temperature affects the tendency of the asphalt to harden during the subsequent carbonization process; that is, the higher the softening point temperature, the harder the carbonized material tends to be. It also affects the yield; a higher softening point temperature results in a higher yield, but also increases costs. Therefore, the requirement for the hard carbon tendency of the second asphalt powder is not strict; soft carbon is sufficient to meet the needs of filling or coating, and its softening point temperature does not need to be too high. Preferably, in some embodiments, the softening point temperature of the first asphalt powder is 180~350℃. Preferably, in some embodiments, the softening point temperature of the second asphalt powder is 60~250℃. Softening point temperatures of both asphalt powders within the above ranges are suitable for obtaining a negative electrode active material with good specific capacity, rate capability, and initial coulombic efficiency under low-cost conditions.

[0072] In some embodiments, in step S1, the temperature of the first heat treatment is 300~550℃; and / or, in step S1, the time of the first heat treatment is 2~4h. It is understood that the temperature of the first heat treatment can be 300℃, 450℃, or 550℃, and the time of the first heat treatment can be 2h, 3h, or 4h. Simultaneously controlling the time and temperature of the first heat treatment within the above ranges solves, to some extent, the problem of poor consistency in the preparation process due to the complex composition of asphalt materials, while ensuring the controllability of the final negative electrode active material structure.

[0073] In some embodiments, in step S1, the particle size distribution of the first asphalt powder is D90≤10 mm. Controlling the particle size distribution of the first asphalt powder to D90≤10 mm can ensure that the first heat treatment is more thorough.

[0074] In some embodiments, in step S21, the oxygen-containing compound includes one or more of sulfuric acid, nitric acid, phosphoric acid, potassium permanganate, acetic acid, ethylene glycol, glycerol, pentaerythritol, ethyl acetate, formaldehyde, paraformaldehyde, p-hydroxybenzaldehyde, sulfur, p-formaldehyde, sodium hydroxide, potassium hydroxide, and lithium hydroxide. It is understood that the oxygen-containing compound can be any one of sulfuric acid, nitric acid, phosphoric acid, potassium permanganate, acetic acid, ethylene glycol, glycerol, pentaerythritol, ethyl acetate, formaldehyde, paraformaldehyde, p-hydroxybenzaldehyde, sulfur, p-formaldehyde, sodium hydroxide, potassium hydroxide, and lithium hydroxide, or two or more of these compounds, all within the scope of this invention. The addition of oxygen-containing compounds effectively inhibits the rearrangement of pitch molecules, reduces the graphitization degree of hard carbon, and increases the interlayer spacing, thereby significantly improving the capacity and rate performance of hard carbon materials. Because the oxygen provided by the oxygen-containing compounds has low reactivity, the reaction tends to proceed along the expected pathway, reducing the possibility of over-oxidation and thus increasing the yield of the target product.

[0075] In some embodiments, in step S21, the temperature of the second heat treatment is 120~150℃; and / or, in step S21, the time of the second heat treatment is 2~8h. It is understood that the temperature of the second heat treatment can be 120℃, 140℃, or 150℃, and the time of the second heat treatment can be 2h, 5h, or 8h. Controlling the time and temperature of the second heat treatment within the above ranges ensures that the oxygen-containing compound sufficiently induces the heavy components in the first intermediate to undergo oxidative cross-linking, forming an amorphous structure. This structure is less prone to graphitization during subsequent carbonization, and the pores in the second intermediate are primarily micropores.

[0076] In some embodiments, in step S21, the mass ratio of the first intermediate, the oxygen-containing compound, and the water is 0.5:1:10 to 5:1:10. This mass ratio within the above range ensures that the second intermediate has a low degree of graphitization and its pores are mainly micropores.

[0077] In some embodiments, in step S21, the particle size distribution of the first intermediate is D10≥5μm, D50≤12μm, and D90≤40μm. D10≥5μm means that 10% of the particles in the first intermediate have a particle size less than or equal to 5μm, D50≤12μm means that 50% of the particles in the first intermediate have a particle size less than or equal to 12μm, and D90≤40μm means that 90% of the particles in the first intermediate have a particle size less than or equal to 40μm. The above particle size distribution can ensure more thorough mixing with oxygen-containing compounds in the subsequent process, so that the macromolecular heavy components in the first intermediate are fully cross-linked to form uniform micropores.

[0078] In some embodiments, in step S221, the inert gas includes one or more of argon, nitrogen, carbon dioxide, and hydrogen. Using an inert gas ensures that the second intermediate is not over-oxidized during carbonization, reducing the occurrence of side reactions.

[0079] In some embodiments, in step S221, the temperature of the first carbonization treatment is 1000~1800℃; and / or, in step S221, the time of the first carbonization treatment is 2~4h. It is understood that the temperature of the first carbonization treatment can be 1000℃, 1500℃, or 1800℃, and the time of the first carbonization treatment can be 2h, 3h, or 4h. Controlling the time and temperature of the first carbonization treatment within the above ranges can ensure that the oxygen-containing compound can sufficiently inhibit the ordered arrangement of the carbon layers in the second intermediate, maintaining its disordered structure as much as possible, thereby reducing the graphitization degree of hard carbon and increasing its specific capacity.

[0080] In some embodiments, in step S222, the organic solvent includes one or more of kerosene, gasoline, diesel, tetrahydrofuran, petroleum ether, methyl chloride, xylene, acetone, methanol, ethanol, n-hexane, carbon tetrachloride, carbon disulfide, turpentine, and benzene. The addition of the above organic solvents reduces the viscosity of the second asphalt powder, which is more conducive to the filling of macropores and mesopores in hard carbon without significantly reducing micropores.

[0081] In some embodiments, in step S222, the mass ratio of the hard carbon, the organic solution containing the second asphalt powder, and the organic solution containing the second asphalt powder in the latter is 5:20:0.1 to 5:40:0.5. This mass ratio within the above range ensures that the second asphalt powder effectively fills the mesopores and macropores in the hard carbon while maintaining the number of micropores.

[0082] In some embodiments, in step S222, the temperature of the second carbonization treatment is 1000~1800℃; and / or, in step S222, the time of the second carbonization treatment is 2~8h. It is understood that the temperature of the second carbonization treatment can be 1200℃, 1400℃, or 1600℃, and the time of the second carbonization treatment can be 4h, 6h, or 8h. Controlling the time and temperature of the second carbonization treatment within the above ranges ensures that the second asphalt powder filling the macropores and mesopores in the hard carbon is fully converted into soft carbon, without affecting the structural consistency of the hard carbon.

[0083] The present invention also provides a sodium-ion battery, wherein the sodium-ion battery comprises the aforementioned negative electrode active material or the negative electrode active material prepared by the aforementioned method for preparing the negative electrode active material. Therefore, the sodium-ion battery possesses all the beneficial effects of the aforementioned negative electrode active material or the method for preparing the negative electrode active material, which will not be elaborated upon here.

[0084] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0085] Example 1

[0086] A negative electrode active material is prepared by the following steps:

[0087] Step (1): Preparation of the first asphalt powder: Asphalt with a softening point of 200℃ is used as a precursor and is simply crushed using a pulverizer until the particle size reaches the requirement of D90≤8mm to obtain the first asphalt powder.

[0088] Step (2): Heat treatment of the first asphalt powder: The first asphalt powder obtained in step (1) is placed in a reactor and heated to 400°C under negative pressure and stirred continuously for 3 hours. After heating, the reactor is naturally cooled to room temperature and then pulverized again to obtain a first intermediate with a particle size distribution of D10≥5μm, D50≤12μm, and D90≤40μm.

[0089] Step (3): Mixing and heat treatment of oxygen-containing compounds: Weigh the first intermediate obtained in step (2), phosphoric acid (as an oxygen-containing compound), and deionized water in a mass ratio of 1:1:10, add them to the reaction vessel, and stir and heat at 150°C for 4 hours. After heating, cool, filter, wash, and dry to obtain the treated second intermediate.

[0090] Step (4): First carbonization treatment: The second intermediate obtained in step (3) is placed in a gas-protected carbonization furnace and carbonized under the protection of a mixed gas of argon and nitrogen. The carbonization temperature is controlled at 1500℃. After carbonization, the furnace is allowed to cool naturally to room temperature and then crushed and sieved to obtain hard carbon powder with D50≤20μm.

[0091] Step (5): Preparation of asphalt-based negative electrode active material: The second asphalt powder (softening point 100℃) was dissolved in tetrahydrofuran (as solvent) to form a homogeneous asphalt solution. Then, the hard carbon powder obtained in step (4) was placed in the asphalt solution, and the solvent was evaporated under stirring. After evaporation, the product was placed in a gas-protected carbonization furnace and carbonized at 1200℃ for 4 hours. After cooling, the negative electrode active material was obtained by sieving.

[0092] Example 2

[0093] The difference between Example 2 and Example 1 is that:

[0094] In step (2), the temperature is heated to 300°C under negative pressure and stirred continuously for 3 hours.

[0095] Example 3

[0096] The difference between Example 3 and Example 1 is that:

[0097] In step (2), the temperature is heated to 550°C under negative pressure and stirred continuously for 3 hours.

[0098] Example 4

[0099] The difference between Example 4 and Example 1 is that:

[0100] In step (3), the mass ratio of the first intermediate, the oxygenated compound and the deionized water is 0.5:1:10.

[0101] Example 5

[0102] The difference between Example 5 and Example 1 is as follows:

[0103] Step (5) is not performed.

[0104] Example 6

[0105] The difference between Example 6 and Example 1 is that:

[0106] Steps (3) and (5) are not performed.

[0107] Comparative Example 1

[0108] The difference between Comparative Example 1 and Example 1 is that:

[0109] Step (2) is not performed.

[0110] Comparative Example 2

[0111] The difference between Comparative Example 2 and Example 1 is that:

[0112] Step (3): Weigh the first intermediate obtained in step (2) and deionized water in a mass ratio of 1:10, add them to the reactor, and stir and heat at 150°C for 4 hours under oxygen conditions.

[0113] Comparative Example 3

[0114] The difference between Comparative Example 3 and Example 1 is that:

[0115] Step (2): Heat to 400°C under normal pressure and stir continuously for 3 hours.

[0116] Comparative Example 4

[0117] The difference between Comparative Example 4 and Example 1 is that:

[0118] In step (5), the second asphalt powder is directly mixed with the hard carbon powder obtained in step (4) and subjected to a second carbonization treatment.

[0119] Performance testing

[0120] The negative electrode active material prepared in Example 1 was observed by scanning electron microscopy, and the results are as follows: Figure 1 As shown.

[0121] Depend on Figure 1 It can be seen that the negative electrode active material prepared in Example 1 is an irregularly shaped block particle that is dense and uniform.

[0122] The negative electrode active materials in Examples 1-6 and Comparative Examples 1-4 were compared, and their porosity, specific surface area, micropore ratio, average pore size, consistency index, and interlayer spacing index were tested. The test methods are as follows:

[0123] (a) Porosity is calculated using the following formula:

[0124] ;

[0125] Where V pores V is the volume of all voids in the material. total The total volume of the material;

[0126] (b) Specific surface area test: nitrogen was used as adsorbent. The specific surface area and pore size distribution of the material were determined by Autosorb-iQ analyzer. The specific surface area was determined by Bruner-Emmett-Teller (BET) method. The pore size was calculated by density functional theory (DFT) method.

[0127] (c) The interlayer spacing was measured using X-ray diffraction (XRD) technology. A Shimadzu XRD-6000 X-ray diffractometer was used with Cu Kα as the radiation source (λ = 1.5406 Å) at a tube voltage of 40 V and a tube current of 40 mA. The diffracting was performed in the range of 5° to 80° with a step size of 0.04° and a diffraction rate of 10°·min. -1 The scanning speed allows for precise scanning and structural analysis of the sample.

[0128] The results are shown in Table 1 and Figure 2 As shown.

[0129] Table 1 Performance tests of the negative electrode active materials in Examples 1-6 and Comparative Examples 1-4

[0130]

[0131] Depend on Figure 2 Two broad diffraction peaks can be observed, located near 24° and 44° respectively. The interlayer spacing of the carbon layers in Example 1 is calculated to be 0.376 nm according to the Bragg equation.

[0132] In summary, this invention enables the control of interlayer spacing and pore distribution in negative electrode active materials.

[0133] The negative electrode active materials from Examples 1-6 and Comparative Examples 1-4 were used to prepare coin-type half-cells for testing. The specific steps were as follows: The negative electrode active material was made into a negative electrode sheet. The preparation method included: mixing the negative electrode active material, acetylene black, and PVDF in a mass ratio of 95:2.5:2.5 to form a slurry; then coating the slurry onto copper foil; subsequently transferring it to a vacuum drying oven at 105°C until the electrode sheet was dry (approximately 4 hours); after drying, cutting it into circular electrode sheets, numbering them, and weighing them; then transferring them to a vacuum drying oven for drying for 4 hours to obtain the negative electrode sheet. A sodium-ion coin cell was assembled by combining a negative electrode, a sodium metal sheet, a GF / C glass fiber separator, and an NP-005 electrolyte. The reversible capacity, initial coulombic efficiency, and rate performance of 10 coin cell sets were measured. The test methods for reversible capacity and initial coulombic efficiency were as follows: a constant current was applied, and the voltage change during the first charge and discharge process was recorded. The test voltage range was 0.0001-3V, and the charge / discharge rate was set to 0.15C to obtain the charge / discharge curves. Figure 3The reversible capacity and initial coulombic efficiency data are shown in Table 2, and the consistency is judged based on the electrochemical performance during the first charge and discharge process. The rate performance test method is as follows: the Xinwei BTS battery tester is used in conjunction with a computer system for real-time detection and analysis. The test voltage range is set to 0.0001-3 V, and the charge and discharge rates are set to 0.1C, 1C, 2C and 3C respectively. The rate performance data results are shown in Table 3.

[0134] Table 2 Performance characterization of coin half-cells corresponding to Examples 1-6 and Comparative Examples 1-4

[0135]

[0136] Table 3. Rate performance characterization of coin half-cells corresponding to Examples 1-6 and Comparative Examples 1-4.

[0137]

[0138] As shown in Table 2, the reversible capacity of the coin cell half-cells prepared in the embodiments of the present invention is 280-360 mAh / g, and the initial coulombic efficiency is 88-94%. As shown in Table 3, the reversible capacity of the coin cell half-cells prepared in the embodiments of the present invention at 1C can reach 256-319 mAh / g. In particular, the coin cell half-cell in Example 1 has a reversible capacity of 360 mAh / g at 0.15C, an initial coulombic efficiency of 94%, and a reversible capacity of 319 mAh / g at 1C.

[0139] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A negative electrode active material, characterized in that, The negative electrode active material includes a porous core material and a shell material that at least fills the pores of the porous core material. The porous core material includes porous hard carbon, and the shell material includes soft carbon. The porosity of the negative electrode active material is 46%~63%, and the proportion of micropores in the pores of the negative electrode active material is 55%~72%; the average pore size of the micropores is 2.1~4.0 Å. The negative electrode active material is prepared by the following steps: S1. The first asphalt powder is subjected to a first heat treatment under negative pressure and then cooled to obtain a first intermediate. S2. Under inert gas conditions, the first intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material; Step S2 includes: S21. The first intermediate, the oxygen-containing compound, and water are mixed, subjected to a second heat treatment, and cooled to obtain a second intermediate; the oxygen-containing compound includes one or more of sulfuric acid, nitric acid, phosphoric acid, potassium permanganate, acetic acid, ethylene glycol, glycerol, pentaerythritol, ethyl acetate, formaldehyde, paraformaldehyde, p-hydroxybenzaldehyde, sulfur, p-formaldehyde, sodium hydroxide, potassium hydroxide, and lithium hydroxide. S22. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material; Step S22 includes: S221. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain hard carbon; S222. The hard carbon is mixed with an organic solution containing the second asphalt powder, the organic solvent is removed, and a mixture is obtained. The mixture is then subjected to a second carbonization treatment to obtain a negative electrode active material.

2. The negative electrode active material as described in claim 1, characterized in that, The specific surface area of ​​the negative electrode active material is 2~25m². 2 / g; and / or, The mass ratio of the porous core material to the shell material is 7:1 to 20:

1.

3. A method for preparing the negative electrode active material as described in claim 1 or 2, characterized in that, Includes the following steps: S1. The first asphalt powder is subjected to a first heat treatment under negative pressure and then cooled to obtain a first intermediate. S2. Under inert gas conditions, the first intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

4. The method for preparing the negative electrode active material as described in claim 3, characterized in that, Step S2 includes: S21. Mix the first intermediate, the oxygen-containing compound and water, perform a second heat treatment, and cool to obtain the second intermediate; S22. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain the negative electrode active material.

5. The method for preparing the negative electrode active material as described in claim 4, characterized in that, Step S22 includes: S221. Under inert gas conditions, the second intermediate is subjected to a first carbonization treatment to obtain hard carbon; S222. The hard carbon is mixed with an organic solution containing the second asphalt powder, the organic solvent is removed, and a mixture is obtained. The mixture is then subjected to a second carbonization treatment to obtain a negative electrode active material.

6. The method for preparing the negative electrode active material as described in claim 5, characterized in that, The temperature of the first carbonization treatment is greater than the temperature of the second carbonization treatment; and / or, The softening point temperature of the first asphalt powder is higher than that of the second asphalt powder.

7. The method for preparing the negative electrode active material as described in claim 5 or 6, characterized in that, The softening point temperature of the first asphalt powder is 180~350℃; and / or, The softening point temperature of the second asphalt powder is 60~250℃.

8. The method for preparing the negative electrode active material as described in claim 4, characterized in that, In step S1, the temperature of the first heat treatment is 300~550℃; and / or, In step S1, the duration of the first heat treatment is 2-4 hours; and / or, In step S1, the particle size distribution of the first asphalt powder is D90 ≤ 10 mm; and / or, In step S21, the oxygen-containing compound includes one or more of the following: sulfuric acid, nitric acid, phosphoric acid, potassium permanganate, acetic acid, ethylene glycol, glycerol, pentaerythritol, ethyl acetate, formaldehyde, paraformaldehyde, p-hydroxybenzaldehyde, sulfur, p-formaldehyde, sodium hydroxide, potassium hydroxide, and lithium hydroxide; and / or, In step S21, the temperature of the second heat treatment is 120~150℃; and / or, In step S21, the duration of the second heat treatment is 2-8 hours; and / or, In step S21, the mass ratio of the first intermediate, the oxygen-containing compound, and the water is 0.5:1:10 to 5:1:10; and / or, In step S21, the particle size distribution of the first intermediate is D10≥5μm, D50≤12μm, and D90≤40μm.

9. The method for preparing the negative electrode active material as described in claim 5, characterized in that, In step S221, the inert gas includes argon; and / or, In step S221, the temperature of the first carbonization treatment is 1000~1800℃; and / or, In step S221, the first carbonization treatment takes 2-4 hours; and / or, In step S222, the organic solvent includes one or more of kerosene, gasoline, diesel, tetrahydrofuran, petroleum ether, methyl chloride, xylene, acetone, methanol, ethanol, n-hexane, carbon tetrachloride, carbon disulfide, turpentine, and benzene; and / or, In step S222, the mass ratio of the hard carbon, the organic solution containing the second asphalt powder, and the organic solution containing the second asphalt powder is 5:20:0.1 to 5:40:0.5; and / or, In step S222, the temperature of the second carbonization treatment is 1000~1800℃; and / or, In step S222, the second carbonization treatment takes 2 to 8 hours.

10. A sodium-ion battery, characterized in that, The sodium-ion battery includes the negative electrode active material as described in any one of claims 1 to 2 or the negative electrode active material prepared by the method described in any one of claims 3 to 9.

Citation Information

Patent Citations

  • Porous hard carbon negative electrode material, preparation method thereof and lithium ion battery

    CN108963253A

  • Porous carbon material and preparation method thereof, lithium ion capacitor positive electrode and lithium ion capacitor

    CN119920630A

  • Porous soft and hard carbon composite material for negative electrode of sodium-ion battery as well as preparation method and application

    CN120208184A

Cited By

  • A porous carbon-based hard carbon material with a rich closed pore hard carbon shell layer, and a preparation method and sodium ion battery application thereof

    CN122646827A